2022
DOI: 10.3389/fendo.2022.960222
|View full text |Cite
|
Sign up to set email alerts
|

25-hydroxyvitamin D and testosterone levels association through body mass index: A cross-sectional study of young men with obesity

Abstract: BackgroundsVitamin D and testosterone deficiency have been widely related to obesity. However, only a few studies have investigated the effect of vitamin D on testosterone in the context of obesity, in which controversial results have been raised.ObjectivesThe purpose of this study was to determine the relationship between serum 25-hydroxyvitamin D (25(OH)D) and testosterone levels in young men with different grade of obesity.Design and methodsThis cross-sectional study included 269 healthy young men with obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(21 reference statements)
0
1
1
Order By: Relevance
“…At first glance, this finding contradicts the data of Damas-Fuentes et al [54], Nimptsch et al [55], and Wehr et al [57] and the general conclusion of a large-scale meta-analysis [56]. However, all our participants were healthy young men, whereas Damas-Fuentes et al [54] reported a significant positive association between serum 25(OH)D and testosterone levels only in men with morbid obesity, and Nimptsch et al [55] and Wehr et al [57] observed such an association in middle-aged and elderly men. A meta-analysis by D'Andrea et al [56] included data from eighteen studies involving 20,576 individuals altogether.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…At first glance, this finding contradicts the data of Damas-Fuentes et al [54], Nimptsch et al [55], and Wehr et al [57] and the general conclusion of a large-scale meta-analysis [56]. However, all our participants were healthy young men, whereas Damas-Fuentes et al [54] reported a significant positive association between serum 25(OH)D and testosterone levels only in men with morbid obesity, and Nimptsch et al [55] and Wehr et al [57] observed such an association in middle-aged and elderly men. A meta-analysis by D'Andrea et al [56] included data from eighteen studies involving 20,576 individuals altogether.…”
Section: Discussioncontrasting
confidence: 77%
“…Previous studies [54,55] and a recent large-scale meta-analysis [56] have revealed a positive association between vitamin D status and serum testosterone levels. In addition to a positive association, Wehr et al [57] reported similar seasonal variation in serum 25(OH)D and testosterone concentrations.…”
Section: Discussionmentioning
confidence: 94%